Examining the effect of stress on the flexible updating of avoidance responses. (15th March 2021) - Lemmens, Anke; Quaedflieg, Conny W. E. M.; Dibbets, Pauline; Rijkeboer, Marleen; Smeets, Tom
Abstract: Acute stress has been found to impair the flexible updating of stimulus − outcome associations. However, there is a lack of studies investigating the effect of acute stress on the flexible updating of stimulus–response associations, like active avoidance responses. The current study used an avoidance reversal learning paradigm to address this question. Sixty‐one participants learned that a red dot was associated with an aversive sound, whereas a green dot was not (Pavlovian Acquisition phase). Next, they were trained to avoid the aversive stimulus by selectively pressing a button in response to the red, but not the green, dot (Avoidance Acquisition phase). Subsequently, participants either underwent a stress induction task or a no‐stress control task. The flexible updating of expectancies of the US and avoidance responses were assessed after reversal of the original contingencies (Reversal Test). Acute stress did not impair the flexible updating of avoidance responses during the Reversal Test. In contrast, results showed that in the stress group the expectancies of the aversive sound were more in accordance with the reversed contingencies compared to the ratings of control participants. Additionally, cortisol responders avoided less often in comparison to cortisol non‐responders. Increased noradrenergic activity in stressed participants was related to impairments in the flexible updating of avoidance responses after contingency reversal, while this association was absent in the control participants. In conclusion, our results suggest that the autonomic response might account for shifting the balance toward inflexible updating of stimulus–outcome awareness while stress does not impair flexible updating of avoidance responses. Abstract : Acute stress did not lead to more habitual avoidance responding. On the contrary, better stimulus–response awareness in a Reversal Test when under stress was observed. Furthermore, findings suggested that impairments in the flexible updating of avoidance responses are related to increased noradrenergic activity in stressed participants.